Evaluation of Making Compulsory Second Foreign Language German Courses Elective in Secondary Education - Karaman, Fatma (Ondokuz Mayıs Üniversitesi, 2025)
Many changes have been made in foreign language education policies in Turkey from past to present. Finally, the Ministry of National Education has made a new change regarding the teaching of German at the secondary education level. With this change, the Ministry of National Education stated in the August 2023 issue of the Announcements magazine that the compulsory second foreign language course will be gradually removed from the compulsory courses and made elective, starting from the 9th grade, as of the 2023-2024 academic year. With this decision, a negative attempt was made to change the policy towards teaching German by making the compulsory second foreign language course, German, an elective course. In this context, the aim of this study is to evaluate the decision to make the second foreign language courses, which are compulsory at the secondary education level, optional as of 2023, in line with the opinions of students and parents who are among the stakeholders affected by this decision. To investigate how this decision was received, positively or negatively, by students and parents. To achieve this aim, the phenomenological method, which is one of the qualitative research methods, was used in the study. In obtaining the data, semi-structured interview technique was used among the data collection techniques. Descriptive analysis was preferred in analyzing the data obtained through the interview technique. As a result of the study, it was determined that both students and parents evaluated this decision negatively in terms of a second foreign language and wanted the German course to continue as a compulsory course again, and that they thought that the students were deprived of the foreign language they would need in their future professional lives by taking away their opportunity to learn German in the school environment.

Geçmişten günümüze kadar Türkiye’de yabancı dil eğitimi politikalarında birçok değişiklik yapılmıştır. Son olarak Milli Eğitim Bakanlığı tarafından ortaöğretim kademesinde Almanca öğretimine ilişkin yeni bir değişikliğe gidilmiştir. Bu değişiklikle Milli Eğitim Bakanlığı Tebliğler dergisinin 2023 Ağustos ayı sayısında zorunlu olan ikinci yabancı dil dersinin 2023-2024 eğitim öğretim yılından itibaren 9. sınıftan başlamak üzere kademeli olarak zorunlu dersler arasından kaldırılarak seçmeli hale getirileceğini belirtmiştir. Bu kararla zorunlu ikinci yabancı dil olan Almanca dersi seçmeli duruma düşürülerek Almanca öğretimine yönelik politikaya olumsuz bir girişimde bulunulmuştur. Bu bağlamda bu çalışmanın amacı ortaöğretim kademesinde zorunlu olan ikinci yabancı dil derslerinin 2023 yılından itibaren seçmeli konuma getirilmesinin bu karardan etkilenen paydaşlardan olan öğrenci ve veli görüşleri doğrultusunda değerlendirmektir. Bu kararın öğrenciler, veliler tarafında olumlu veya olumsuz olmak üzere nasıl karşılandığını araştırmaktır. Bu amaca ulaşmak için çalışmada nitel araştırma yöntemlerinden olan olgubilim yöntemi kullanılmıştır. Verilerin elde edilmesinde veri toplama tekniklerinden yarı yapılandırılmış görüşme tekniğinden faydalanılmıştır. Görüşme tekniğiyle elde edilen verilerin analiz edilmesinde betimsel analiz tercih edilmiştir. Çalışmanın sonucunda hem öğrencilerin hem de velilerin alınan bu kararı ikinci yabancı dil açısından olumsuz değerlendirerek Almanca dersinin tekrar zorunlu ders olarak devam etmesini istedikleri, öğrencilerin okul ortamında Almanca öğrenme imkânlarının ellerinden alınarak gelecekte mesleki yaşamlarında ihtiyaç duyacakları yabancı dilden mahrum bırakıldıklarını düşündükleri belirlenmiştir.
Ortaöğretimde Zorunlu İkinci Yabancı Dil Almanca Derslerinin Seçmeli Duruma Getirilmesinin Değerlendirilmesi
Keywords: Turkish and Social Sciences Education (Diğer); Türkçe ve Sosyal Bilimler Eğitimi (Diğer)